2018
DOI: 10.1016/j.jaad.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of skin cancer in patients with HIV: A Danish nationwide cohort study

Abstract: Patients with HIV have an increased risk of BCC and SCC. Low nadir, but not current, CD4 cell count as a marker of immunosuppression was associated with an increased risk of SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 16 publications
1
35
0
3
Order By: Relevance
“…An equivalent study in Denmark revealed a five-fold increase in SCC rate and a 1.8-fold increase in BCC in HIV-positive patients [39]. Recent reports investigating the risk of CM in White HIV-positive patients in North America [40] and Denmark [39] found no difference compared with the general population. As is the case for CM in immunocompetent individuals, older age and higher sun exposure were associated with an increased risk [40].…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 97%
See 1 more Smart Citation
“…An equivalent study in Denmark revealed a five-fold increase in SCC rate and a 1.8-fold increase in BCC in HIV-positive patients [39]. Recent reports investigating the risk of CM in White HIV-positive patients in North America [40] and Denmark [39] found no difference compared with the general population. As is the case for CM in immunocompetent individuals, older age and higher sun exposure were associated with an increased risk [40].…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 97%
“…Studies in California demonstrated that there was a greater than two-fold higher incidence of SCC, but not of BCC, in White HIV-positive patients compared with White HIV-negative controls [37,38]. An equivalent study in Denmark revealed a five-fold increase in SCC rate and a 1.8-fold increase in BCC in HIV-positive patients [39]. Recent reports investigating the risk of CM in White HIV-positive patients in North America [40] and Denmark [39] found no difference compared with the general population.…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 98%
“…e Odds Ratio for PLHIV to develop KS in SA was reported as 134 [18]. PLHIV are also at higher risk for developing NMSC with a 5-fold increased risk of SCC [18,19]. is may also explain the lower BCC to SCC ratio as mentioned.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the rollout of the antiretroviral therapy (ART) programme in South Africa in 2004 the risk of KS amongst PLHIV remains elevated even in the ART era [18]. Omland et al also observed a 2-fold increased risk of BCC and a 5-fold increased risk of SCC in PLHIV compared with the background population [19]. e increasing incidence of skin cancers places major financial strain on South Africa's already overburdened public healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı enfeksiyonların da deri kanseri açısından risk oluşturduğu bilinmektedir. HIV pozitif bireylerde BHK riski yaklaşık 2 kat, SHK riski yaklaşık 5 kat artmış olarak bulunmuştur (Omland et al, 2018). Chen ve ark.…”
unclassified